The Genealogy of the Labor Hoarding Concept - Jeff E. Biddle (Duke University, Center for the History of Political Economy (CHOPE), 2014)
The modern concept of labor hoarding emerged in early 1960s, and soon became a standard part of mainstream economists' explan ation of the working of labor markets. The concept represents the convergence of three importa nt elements: an empirical fi nding that labor productivity was procyclical; a framing of this fi nding as a "puzzle" or anomaly fo r the basic neoclassical theory of the firm, and a proposed resolu tion of the puzzle based on optimizing behavior of the firm in the presence of costs of hiring, firing, and training workers. Th is paper recounts the history of each of these elements, and how they were woven together into the labor hoarding concept. Each history involves people associated with various research traditions and motivated by an array of questions, many of which were unrelated to the qu estions that the modern labor hoarding concept was ultimately created to address.
Keywords: B2; 330; labor hoarding; productivity; business cycles